Usefulness of Comprehensive Income Statement - Preliminary Study on the Example of Companies from the WIG30 Index - Przemysław Czajor; Piotr Druszcz; Michał Hendryk (Nauki o Finansach)
The financial result of a company is undoubtedly the most frequently analyzed category in making economic decisions. The changing needs of financial statements users resulted in the replacement of the classic financial result with the broader concept of comprehensive income, which was regulated in the International Accounting Standard 1 Presentation of financial statements. As a result a statement of the entity's comprehensive income is created. An important element analyzed by the scientific community is the presentation of the mentioned comprehensive income and its usefulness. The purpose of the article is to determine the impact of introducing the obligation to prepare a statement of comprehensive income on the usefulness of the financial statement. The usefulness has been assessed from the perspective of the form of statement of comprehensive income and the relevance of other comprehensive income's items as compared with net income.(original abstract)